Pneumatosis Intestinalis and Pneumoperitoneum After Lung Transplantation: Single-Center Experience and Systematic Review - Hiroshi Kagawa; Masashi Furukawa; Ernest G. Chan; Matthew Morrell; Pablo G. Sanchez (Journal of Transplantation)
Conclusions: This report has the largest number of patients so far with PI and pneumoperitoneum after LT. These conditions have a high rejection and high mortality rate. Mechanical ventilation, tracheostomy, gastrointestinal procedure, CMV infection, Clostridium difficile (C. difficile) infection, and immunosuppression can be the risk factors, and the management includes laparotomy or conservative management. It is generally recommended to proceed with laparotomy if patients have portal venous gas, elevated white blood cell count, elevated lactic acid level, decreased bicarbonate level, elevated amylase level, metabolic acidosis, abdominal tenderness, or abdominal distension. Otherwise, most of the patients recover with conservative management with nil per os (NPO), metronidazole, ganciclovir, antibiotics, high-flow oxygen, and holding mycophenolate mofetil (MMF).